TRANSPLANTATION OF GIANT GOURAMY (Osphronemus gouramy) TESTICULAR CELLS IN EARLY HATCHING TILAPIA (Oreochromis niloticus) LARVAE - Jasmadi Jasmadi; Odang Carman; Alimuddin Alimuddin (Pusbindiklat - LIPI, 2016)
Cell transplantation technology has been widely developed in mammals, but less implemented in inland aquaculture fish. Giant gouramy (Osphronemus gouramy) is one of important comercial aquaculture commodities that has a relatively long first reproductive cycle compared to the tilapia (Oreochromis niloticus). Tilapia has a faster reproductive cycle and potential as giant gouramy surrogate broodstock. This study was aimed to applicate testicular cell transplantation technology of giant gouramy in tilapia larvae and to evaluate its success rate trough donor cell colonization. Tilapia larvae of 1-2 dph (days post hatching) and 3-4 dph were injected with ±20.000 giant gouramy testicular cells in the peritoneal cavity, and then groomed for two months. Cell colonization of spermatogonium donor was determined by Polymerase Chain Reaction (PCR), using giant gouramy F1-Growth Hormone and R1-Growth Hormone primers. The result of cell dissociation showed that a bigger giant gouramy (827 g) had lower of spermatogonia composition (4.45%) than a smaller gouramy (608 g) (14.96%). Donor cell colonization in 1-2 dph recipient was higher (100%) than in 3-4 dph recipient (75%). Whereas recipient Survival Rate (SR) was 89.34% for 1-2 dph recipient and 98.96% for 3-4 dph recipient respectively. This study suggests that testicular cell transplantation technology of giant gouramy could be appllied to tilapia (Xenotransplantation) and cell transplantation has a better performance in 1-2 dph than in 3-4 dph recipients. With such success, there is a high potential that the giant gouramy cultivation can be increased through the cell transplantation technology.